A MORPHOLOGICAL APPROACH TO REVEAL THE ARCHITECTURAL IDENTITY OF THE HISTORICAL ALGERIAN RAILWAY STATIONS (XIX AND XX CENTURIES) - Kebbour Akram,; Bioud Ghofrane,; Nasri Manel,; Bouzaher Soumia, (International Journal of Innovative Technologies in Social Science, 2024)
In the annals of railway architecture, the railway station emerges as a prominent edifice replete with profound symbolism, encapsulating a pivotal epoch in the annals of human history, notably the Industrial Revolution (RAISTRICK, 1972). Internationally, its architectural manifestations have evolved in tandem with temporal and geographical contexts, serving as a quintessential testament to the advancements in construction technology while mirroring the artistic, political, and socio-economic undercurrents of its era (BOWIE, 1987). Focused on Algeria's railway heritage, this research delves into select colonial-era stations. It aims to unveil morphological, historical and architectural aspects, shaping Algeria's railway identity. The study extends from Algiers to Touggourt, examining key terminals and stations. Ultimately, it seeks a deeper understanding of Algeria's railway evolution. The study discerned multiple categories and subcategories of railway stations. It revealed that Algerian railway stations exhibit a notable architectural heterogeneity that defies facile categorization into a singular, standardized formal or stylistic archetype. Furthermore, this investigation underscored the primary determinants contributing to these divergences, notably the imperatives of defense (both in terms of security and military considerations) and local regional characteristics. Ultimately, this discovery portends the possibility of a distinctive genre of railway architecture local to Algeria emerging from the confluence of these influences and architectural diversity.